Peran Konselor dalam Pendidikan Karakter - Sari, Eka (Jurnal Bimbingan dan Konseling Terapan, 2022)
This research aims to provide an overview of the problem of the role of school counselors related to the implementation of character education. In research using qualitative methods with literature review studies or literature studies. The results of this study show that the implementation of character development begins with the formation of the basic values and norms that exist in society according to state regulations. In its implementation, character education must involve all educators in schools so that the goals of national education can be achieved, one of which is a counselor. The position of school counselors as educators is stated in the 2003 National Education System Law. School counselors' efforts to play a role in implementing character education include consultants acting as examples, problem solvers, and mediators. The application of character education through guidance and counseling counselors has the aim of forming, developing, and increasing character points in students. In the application of character education, some points are emphasized and this is in line with the services of counseling guidance namely learning, personal, social, and career.